Comprehensive school-based intervention: Reducing bullying incidents at SMP Negeri 8 Baubau - Suruambo, Juharmin; Alim, Juflyn; Indrawan, Yongky (Community Empowerment, 2025)
In response to the high number of bullying incidents at SMP Negeri 8 Baubau, this community service program aims to reduce these incidents through a comprehensive approach involving students, teachers, and parents. The program is implemented through outreach, practical skills training, and ongoing mentoring. Evaluations show an increase in participant knowledge (30% among students, 40% among teachers), a decrease in reported bullying cases, and a more positive attitude towards prevention. These results imply that this collaborative and comprehensive approach is effective in building a safe and supportive school culture and can be replicated in other schools.